PARTITIONING OF TRACE ELEMENTS BETWEEN CARBONATE-SILICATE MELTS AND MANTLE MINERALS: EXPERIMENT AND PETROLOGICAL CONSEQUENCES - Girnis A.V.; Bulatov V.K.; Lahaye Y.; Brey G.P. (My University, 2006)
The partitioning of a number of trace elements (Ba, Nb, Zr, Y, REE, etc.) between orthopyroxene, garnet, and carbonate-silicate melt was experimentally studied using a belt apparatus at pressures of 3.5-4.2 GPa and temperatures of 1300-1500°C. The experimental products were investigated by electron microprobe analysis and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The experimental melts varied from carbonatitic (~5 wt % SiO2) at low temperatures (1300-1350°C) to kimberlitic compositions (30 wt % SiO2) at high temperatures (1500°C). The partition coefficients of most elements between orthopyroxene and melt (D iOpx/L ) and garnet and melt (D iGrt/L ) were almost independent of melt composition (temperature). The D iOpx/L values ranged from <0.01 for the most incompatible Ba and light REE to 0.02-0.08 for moderately incompatible Zr, Y, and heavy REE. The D iGrt/L values were approximately an order of magnitude higher, ~0.07 for light REE, 0.7 for Y, and 1.5 for Yb. The character of D iGrt/L variations in the systems studied is in general similar to that established for silicate melts without volatile components. However, the differences in the behavior of moderately incompatible and compatible elements (e.g., light and heavy REE) in the experimental systems are less pronounced compared with CO2-free systems. Considering carbonate-silicate and silicate melts as possible agents of mantle metasomatism, it can be concluded that the former can efficiently transport heavy REE, and the latter have a greater affinity for Nb, Ba, and light REE. A characteristic feature of mantle rocks enriched by carbonate-silicate melts is high Ba/La ratio coupled with relatively weakly fractionated REE distribution patterns. It was shown that the high degrees of enrichment observed in natural kimberlites can be explained by a two-stage scenario, including a preliminary invasion of carbonate-silicate melt into depleted harzburgites in the lower parts of the lithosphere and subsequent very low degree melting. © Pleiades Publishing, Inc., 2006.